Pengaruh Variasi Usia Telur, Higiene Dan Sanitasi Terhadap Kualitas Fisik Dan Mikrobiologis Telur Ayam Ras Yang Beredar Di Pasar Tradisional Kota Kupang - MARIA ANASTASIA NOVIA WOI; Novalino H. G. Kallau; Diana A Wuri (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
This study aims to determine and identify the effect of variations in the age of broiler eggs on the physical and microbiological quality of eggs as well as the state of hygiene and sanitation at the traditional market for selling eggs in Kupang City (Pasar Kasih-Naikoten 1, Pasar Oeba, Oebobo Market, Oesapa Market, and Pasar Oesapa). Penfui). The samples used in this study were 68 respondents and 68 samples of broiler eggs. Data were analyzed descriptively. Variations in egg age are divided into producers and distributors. Physical quality parameters observed were egg weight, egg yolk index, egg white index, Haugh Unit, and pH. The microbiological quality parameter observed was the amount of microbial contamination in eggs. The results of the physical and microbiological quality test of eggs from producers have a better value than distributors because the age of eggs from producers is younger than distributors. The effect of variations in egg age on physical and microbiological quality showed that the longer the age of the eggs, the egg weight, egg white index, yolk index and Haugh Unit decreased. Meanwhile, the longer the age of the eggs, the pH and the amount of microbial contamination will increase. Of the five markets where samples were taken, eggs in the Oebobo Market that came from producers had a shorter egg age variation so that the results of the physical quality test (meets all 6 parameters) and microbiological (1.8x104 cfu/gr) were the best. Meanwhile, hygiene and sanitation factors are more at risk of affecting the microbiological quality of eggs. The hygiene and sanitation of broiler eggs in the Kupang City Traditional Market is quite low due to the lack of information on handling good hygiene and sanitation for broiler egg traders.